CRISPR-HOLMES-based NAD+ detection - Zhuang, Songkuan; Hu, Tianshuai; Zhou, Hongzhong; He, Shiping; Li, Jie; Zhang, Yuehui; Gu, Dayong; Xu, Yong; Chen, Yijian; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2024)
Studies have indicated that the intracellular nicotinamide adenine dinucleotide (NAD+) level is associated with the occurrence and development of many diseases. However, traditional nicotinamide adenine dinucleotide (NAD+) detection techniques are time-consuming and may require large and expensive instruments. We recently found that the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas12a protein can be inactivated by AcrVA5-mediated acetylation and reactivated by CobB, using NAD+ as the co-factor. Therefore, in this study, we created a CRISPR-Cas12a-based one-step HOLMES(NAD+) system for rapid and convenient NAD+ detection with the employment of both acetylated Cas12a and CobB. In HOLMES(NAD+), acetylated Cas12a loses its trans-cleavage activities and can be reactivated by CobB in the presence of NAD+, cutting ssDNA reporters to generate fluorescence signals. HOLMES(NAD+) shows both sensitivity and specificity in NAD+ detection and can be used for quantitative determination of intracellular NAD+ concentrations. Therefore, HOLMES(NAD+) not only provides a convenient and rapid approach for target NAD+ quantitation but also expands the application scenarios of HOLMES to non-nucleic acid detection.